Efeitos dos extratos hidroalcoólicos liofilizados da casca do fruto de Spondias mombin Linn. E Spondias tuberosa Arruda em modelo de senescência induzida por d-galactose em cultura primária de células endoteliais isoladas da artéria aorta de ratos - Souza Júnior, Javanyr Frederico de (2023)
Aging is a natural process with multifactorial causes. As we age, cells to enter a state known as senescence and it increases in number in the body. This occurs in the same way in the vascular endothelium, and one of the regulators in this process is oxidative stress, which leads to endothelial dysfunction and the appearance of age-related cardiovascular diseases. Natural products with antioxidant activity have demonstrated beneficial effects on the cardiovascular system. Therefore, the search for compounds with antioxidant and antisenescent activity in this field should be explored. The literature shows that fruit trees such as Spondias mombin Linn (cajazeira) and Spondias tuberosa Arruda (umbuzeiro) have a good amount of phenolic compounds with antioxidant character. No study has been designed to investigate the antisenescent capacity involving these plants.The objective of this work was to evaluate the effects of lyophilized hydroalcoholic extracts from the fruit peels of Spondias mombin Linn (EHLSM) and Spondias tuberosa Arruda (EHLST) in a model of senescence induced by D-Galactose in a primary culture of endothelial cells isolated from the aorta artery of rats (RAECs). Tests were carried out to determine the total phenolic content, DPPH• radical scavenging activity and identification and quantification of phenolic compounds by high performance liquid chromatography. The cultivated RAECs were divided in two groups: Basal (treated only with EHLSM or EHLST extracts at concentrations 0.01; 0.05; 0.1; 0.5 to 1.0 μg/mL) and D-Galactose (challenged with D-gal 20 mg/mL and treated with EHLSM or EHLST extracts at concentrations 0.01; 0.05; 0.1; 0.5 to 1.0 μg/mL) for 48 hours to assess viability cells, cellular senescence and production of superoxide anions. EHLSM and EHSLT showed a high content of total phenolics, scavenging capacity of DPPH• radicals, and several phenolic compounds were found and quantified. In the Basal group to cell viability assay, the treatment with EHLSM (1.0 μg/mL) and EHLST (0.1, 0.5 and 1.0 μg/mL) reduced viability when compared to the control (p<0.05). In the D-Galactose group, D-gal reduced cell viability when compared to control, the treatment with EHLSM (0.5μg/mL) and EHLST (0.5 and 1.0μg/mL) reduced viability when compared to D-gal (p<0.05). In the SA-β-gal assay of Basal group, no one of the extracts was able to alter senescence. In the D-Galactose group, D-gal increased the percentage of senescent cells when compared to the control, EHLSM (0.1, 0.5 and 1.0μg/mL) and EHLST (0.05, 0.1, 0.5 and 1.0μg/mL) decreased the percentage of senescent cells when compared to D-gal (p<0.05). In the Basal group to superoxide anion production assay, EHLSM (0.5 and 1.0μg⁄mL) and EHLST (0.05, 0.1, 0.5 and 1.0μg⁄mL) increased the production of superoxide anions when compared to the control (p<0.05). In the D-galactose group, D-gal increased the production of superoxide anions when compared to the control, EHLSM (0.1, 0.5 and 1.0 μg/mL) and EHSLT (0.05, 0.1, 0, 5 and 1.0 μg/mL) decreased the production of superoxide anions when compared to D-gal (p<0.05). These results demonstrate that EHLSM and EHLST extracts have antisenescent activity in RAECs challenged with D-gal, and that this activity may be related, at least in part, to the antioxidant capacity of the extracts.